Gallery - Teresa Pereira; Jéssica Bispo (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
Gallery with a few photographs of the Conference on Victorian and American Myth in Videogames.